The effect of different dietary protein levels on the water quality and reproductive performance of Nile tilapia (Oreochromis niloticus) broodstock in biofloc system - Ghaedi, Alireza; Khanjani, Mohammad Hossein (Journal of Fisheries, 2025)
This study investigated the effect of protein levels on the water quality and reproductive performance of Nile tilapia (Oreochromis niloticus) in the biofloc system. Three isocaloric diets with different protein levels (32%, 38%, and 44%) were formulated. A total of nine one-tone tanks with a water holding capacity of 0.9 tons were prepared and equipped with the necessary materials to form biofloc. Seventy-two female and thirty-six male fish were tagged, numbered, and randomly released into the tanks at a female: male ratio of 2:1. The results showed that the lowest amount of TAN (0.21 mgL–1), NO2, and NO3 were observed in the treatment of 32% protein. Mean final weight in the 32% and 38% treatments was 350 and 356 g, respectively, with no significant difference. The highest absolute fecundity (654) was observed in the 32% group, but no significant difference was found between the absolute fecundity of the 38% and 44% groups. The longest interval (17.8 days) was observed in the 44% protein group. The percentage of fertilization and hatching did not significantly differ between the groups. The highest percentage of fertilization (93%) and hatching (89%) were observed in the 32% protein group. The total number of eggs per female fish did not differ between the 32% (12840) and 38% (12670) groups, while the 44% group had the lowest number of eggs (12040). The present study showed that a dietary protein level of 32% is optimal for water quality and reproductive performance of Nile tilapia in the biofloc system.